2019
DOI: 10.1007/s11356-019-07045-2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of anticancer drugs in the aquatic environment: a systematic review

Abstract: Water contamination with pharmaceutical products is a well-studied problem. Numerous studies have demonstrated the presence of anticancer drugs in different water resources that failed to be eliminated by conventional wastewater treatment plants. The purpose of this report was to conduct a systematic review of anticancer drugs in the aquatic environment. The methodology adopted was carried out in compliance with the PRISMA guidelines. From the 75 studies that met the specific requirements for inclusion, data e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…In the last few decades, pharmaceuticals have been saving millions of lives and have emerged as a new class of environmental contaminant [1][2][3][4]. Since 1990, major efforts have been made to study the risks, occurrence, and fate of human pharmaceuticals (identified as pseudo-persistent compounds) which are constantly released in the environment [1,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few decades, pharmaceuticals have been saving millions of lives and have emerged as a new class of environmental contaminant [1][2][3][4]. Since 1990, major efforts have been made to study the risks, occurrence, and fate of human pharmaceuticals (identified as pseudo-persistent compounds) which are constantly released in the environment [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy drugs are a specific group of pharmaceutical compounds used to treat cancer diseases. They are often called anticancer drugs and have been shown to have potent cytotoxic, genotoxic, mutagenic, carcinogenic, endocrine disruptor, and/or teratogenic effects in several organisms, since they have been mainly designed to disrupt or prevent cellular proliferation, usually by interfering in DNA synthesis [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, compounds 6 and 7 affect the resumption of oocyte meiosis triggered by progesterone. It was previously reported that apoptosis occurred in progesterone-treated oocyte 48 h after the completion of maturation [39,40]. Two apoptosis markers, the cleaved caspase 3 [44,45] and the Ser14 phosphorylated histone H2B [44][45][46][47] were detected in prophase I oocytes exposed to compound 7 and in oocytes treated by progesterone and compounds 6 or 7 showing an apoptosis death.…”
Section: Discussionmentioning
confidence: 80%
“…The increasing use of pharmaceuticals results in increased discharges and aquatic contamination [35], for example in Brazil doses up to 123.5 µg/L were measured [39], but higher concentrations all over the world were also reported (see [40] for a review). Xenopus oocytes (M-Phase entry and meiotic maturation from prophase I to metaphase II) offer a unique physiological aquatic model to assess the effects of novel synthesized products on cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Since conventional water and wastewater treatment processes (WWTP) are incapable of completely removing pharmaceuticals, it is therefore important for advanced treatment techniques to be incorporated into WWTPs. Some of the advanced processes that have -27-212 ng/L Surface water/UK [33] Cardiovascular Metoprolol Since conventional water and wastewater treatment processes (WWTP) are incapable of completely removing pharmaceuticals, it is therefore important for advanced treatment techniques to be incorporated into WWTPs. Some of the advanced processes that have 43.0-47.4 mg/L; Ceriodaphnia dubia 20-116 ng/L Surface water/Hungry [34] Antidiabetics Metformin Since conventional water and wastewater treatment processes (WWTP) are incapable of completely removing pharmaceuticals, it is therefore important for advanced treatment techniques to be incorporated into WWTPs.…”
Section: Introductionmentioning
confidence: 99%